2011
DOI: 10.1111/j.1537-2995.2010.03033.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing blood donation intentions using multimedia donor education materials

Abstract: Blood donation coping materials, presented in either written or audiovisual formats, significantly enhance willingness to donate blood among young adults regardless of their initial attitudes toward blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 22 publications
(36 reference statements)
8
66
0
2
Order By: Relevance
“…highlighted the importance of cultural taboos in Pakistan that prevent women from donating blood, and it is only in inevitable circumstances when women are required to donate blood. [17] Bani and Giussani reported that two factors; higher rate of deferrals and adverse reactions in women are responsible for low proportion of female donors. [18] In university students, the two aforementioned factors may be the primary cause of a low number of female donors and cultural taboos may not be important because of higher educational and socioeconomic status as compared to general population.…”
Section: Discussionmentioning
confidence: 99%
“…highlighted the importance of cultural taboos in Pakistan that prevent women from donating blood, and it is only in inevitable circumstances when women are required to donate blood. [17] Bani and Giussani reported that two factors; higher rate of deferrals and adverse reactions in women are responsible for low proportion of female donors. [18] In university students, the two aforementioned factors may be the primary cause of a low number of female donors and cultural taboos may not be important because of higher educational and socioeconomic status as compared to general population.…”
Section: Discussionmentioning
confidence: 99%
“…The insufficient supply of blood from volunteer donors means that many hospitals still need to supplement supplies from BTS with locally collected donations [25]. There is consequently a need to recruit and retain more blood donors, which has traditionally been done using methods such as brochures [26] or videos [27]. In Pakistan, a web-based information system was developed to enable users to search for, collect and donate blood [28], apps related to BD could help attract more volunteers, especially young donors [29].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also improved communications to donors through an enhanced donor recruitment brochure [63,67], use of a video [68], or through a better website [69]. The goals for each of these improvements were to reduce fear, decrease vasovagal reaction rates, and increase blood donor retention.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
“…In another study, the authors explored the use of the same brochure, a video, or a combination of new brochure and video to increase donor recruitment in 599 college students (62% women, 49% never donated) [68]. Both the new brochure and video improved anxiety, attitude, donation confidence, and donation intention to the same degree.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%